Near patient tests for Helicobacter pylori in primary care: How accurate do thev need to be? - Delaney, B; Hobbs, F (1998)
Objectives: To model cost-effectiveness of near patient tests (NPT) for H. pylori in screening proven cases of peptic ulcer disease (PUD) and in the management of new cases of dyspepsia, in order to establish minimum standards for the performance characteristics of NPTs. NPTs may allow more accurate diagnosis to guide appropriate management options and thus influence the costs of treating both new and existing cases of dyspepsia. However, there are confusing data over whether these tests perform adequately. Methods: Decision analysis using a Markov cost-effectiveness model to determine costs and likely PUD recurrence rates for the competing strategies. Results: For patients with previously proven PUD, giving H. pylori eradication therapy to all patients was more cost-effective than using a NPT. "Payback" time was 14 months, dependent on the cure rate of eradication therapy and the rate of co-existing non-ulcer dyspepsia (NUD). For previously uninvestigated cases of dyspepsia, the use of NPT was more cost-effective than endoscopy in all cases. Payback time varied from 6 years 6 months to 1 year 5 months, depending on the cost of maintenance therapy. The NPT would require a minimum sensitivity of 70% to achieve this result; specificity was not important in this context. Conclusions: Based on reported evaluations, all current NPTs for H. pylori meet the performance standard required for selecting dyspeptic patients for endoscopy. On these data, all patients with proven PUD should receive eradication therapy without prior NPT. Eur J Gen Pract 1998;4:149-54. © 1998 Informa UK Ltd All rights reserved.